A brief Patient-Reported Outcomes Quality of Life (PROQOL) instrument to improve patient care. - Jennifer L Ridgeway (Public Library of Science (PLoS), 2013)
Jeff Sloan and colleagues describe the development of the Patient-Reported Outcomes Quality of Life (PROQOL) instrument, which captures and stores patient-recorded outcomes in the medical record for patients with diabetes. Please see later in the article for the Editors' Summary.